Emerging Applications of Elemental 2D Materials. Issue 7 (31st October 2019) - Glavin, Nicholas R.; Rao, Rahul; Varshney, Vikas; Bianco, Elisabeth; Apte, Amey; Roy, Ajit; Ringe, Emilie; Ajayan, Pulickel M.
Abstract: As elemental main group materials (i.e., silicon and germanium) have dominated the field of modern electronics, their monolayer 2D analogues have shown great promise for next‐generation electronic materials as well as potential game‐changing properties for optoelectronics, energy, and beyond. These atomically thin materials composed of single atomic variants of group III through group VI elements on the periodic table have already demonstrated exciting properties such as near‐room‐temperature topological insulation in bismuthene, extremely high electron mobilities in phosphorene and silicone, and substantial Li‐ion storage capability in borophene. Isolation of these materials within the postgraphene era began with silicene in 2010 and quickly progressed to the experimental identification or theoretical prediction of 15 of the 18 main group elements existing as solids at standard pressure and temperatures. This review first focuses on the significance of defects/functionalization, discussion of different allotropes, and overarching structure–property relationships of 2D main group elemental materials. Then, a complete review of emerging applications in electronics, sensing, spintronics, plasmonics, photodetectors, ultrafast lasers, batteries, supercapacitors, and thermoelectrics is presented by application type, including detailed descriptions of how the material properties may be tailored toward each specific application. Abstract : Elemental 2D materials are some of the more exciting nanomaterials of interest due to their unique and tailorable properties. Recent progress in these exciting materials relative to their potential impact in applications including electronics, optoelectronics, and energy systems is presented.